Systematic Review of Pertussis: Trends, Challenges, and Advances in Care and Prevention - Garbarczyk, Wiktor; Napieralska, Agnieszka; Kapla, Albert; Černohorská, Alicja; Bednarczyk, Daria; Białeta, Julia; Siembab, Karolina; Rowińska, Katarzyna; Jurkiewicz, Michalina; Pysiewicz, Wiktoria (Journal of Education, Health and Sport, 2025)
Pertussis, or whooping cough, persists as a significant public health issue despite widespread vaccination. This review examines the disease’s epidemiology, clinical challenges, diagnostic advancements, treatment, and prevention. Increasing incidence among adolescents and adults highlights the impact of waning immunity and gaps in vaccine coverage. Early diagnosis remains difficult due to nonspecific symptoms, though tools like PCR have improved detection. Macrolide antibiotics are the mainstay of treatment, but delayed diagnosis reduces their effectiveness. The emergence of antibiotic-resistant Bordetella pertussis strains is concerning. Preventive measures, such as maternal immunization and booster doses, have shown effectiveness but require optimization. Acellular vaccines, while safer than whole-cell vaccines, exhibit waning immunity, prompting research into next-generation vaccines. This review underscores the need for improved vaccination strategies, public health initiatives to combat vaccine hesitancy, and enhanced global surveillance. Addressing these challenges is vital to reducing pertussis’s burden and improving outcomes, providing critical insights for policy and future research.